Efficacy of Static Progressive Splinting in the Management of Metacarpophalangeal Joint Stiffness: A Pilot Clinical Trial - Jun Wang; Gard Erlandsson; Yong-Jun Rui; Cecilia Li-Tsang (SAGE Publishing, 2014)
Objective: To evaluate the efficacy of a static progressive metacarpophalangeal (MCP) joint flexion splint in managing MCP joint stiffness in patients suffering from traumatized hands. Methods: A total of 31 patients with stiff MCP joints (n = 116) were recruited for this prospective study. A static progressive MCP flexion splint was designed to manage the MCP joint stiffness of traumatized hands, which is a common problem after surgery. The values of the initial and final passive range of motion (PROM) and active range of motion (AROM) were compared. In addition, the Disabilities of the Arm, Shoulder, and Hand (DASH) scores before and after surgery were also compared. Spearman correlation matrix was used to determine the relationship of the DASH score with PROM and AROM separately. Results: The PROM increased from 23.47 ± 16.26 degrees to 59.01 ± 14.75 degrees after treatment, and the difference between the initial and final PROM is 35.54 ± 16.92 degrees (t = 22.63, p < .001, df = 115). The AROM also significantly increased from 10.29 ± 10.67 degrees to 25.03 ± 18.25 degrees, with a mean difference of 14.74 ± 15.40 degrees (t = 10.31, p < .001, df = 115). The DASH score improved from 40.71 ± 13.22 to 24.26 ± 11.33 (t = 7.00, p < .001, df = 30), which indicates a significant negative correlation with the AROM of MCP joints following treatment. Conclusion: The static progressive MCP flexion splint promotes both physical and functional outcomes. The increased AROM of the MCP joints improves the functional outcomes in patients with traumatized hands.